COMPUTER NETWORK CONNECTING WITH THE PERSONAL COMPUTER (PC) - Abdul Jamal Fauzi; Drs. Lingga Hermanto, MM Drs. Lingga Hermanto, MM (Jurnal Sistem Komputer, 1997)
Skytel operations in Indonesia have access to data located in several separate cities,namely Jakarta, Bandung, Semarang, Surabaya, Denpasar and Medan. At the headoffice (Jakarta) terdapt two backbone, where a backbone is used to addressoperational problems (sending information) and the backbone, the other is used tohandle the administration. Each branch office is connected to one backbone, only thecentral office, which handles the operational backbone only, while the backbone thathandles all administrative issues held by the central office. In order for the localnetwork can access the branch office network backbone system of localadministration head office or vice versa, then the media needed to be able to connectthe computer networks of two or more of these. In this case the media is a computernetwork connecting Personal Computers (PCs) which are set as a router using theUNIX operating system.